Effectiveness of Environmental Law in Indonesia: Study on the Implementation of Law Enforcement in Cases of Environmental Damage - Yunita, Sri; Lumbantoruan, Lamtiurma; Kaban, Hairen Br; Pandiangan, Putri Patricia; Ester, Ester; Ndaha, Gebytha Yani; Sihotang, Josep Raja Oloan (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Environmental law enforcement in Indonesia often faces major challenges, especially in terms of implementation and consistency in the field. This research aims to document the effectiveness of environmental law in Deli Serdang Regency, North Sumatra, with a focus on the Jl. Williem Iskandar, New Memories, District. Percut Sei Tuan. The methods used in this research include direct observation and in-depth interviews with local residents and the Environmental Service (DLH). The research results show that although there are regulations governing environmental law, the effectiveness of their implementation is still very limited. Factors that influence this effectiveness include weak supervision, strict sanctions, and low public awareness. The results of this research recommend increased coordination between agencies, more active community involvement, and the application of stricter sanctions to achieve optimal environmental law effectiveness.